2013
DOI: 10.1093/ntr/nts338
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Trajectories Across High School: Sensation Seeking and Hookah Use

Abstract: introduction: This study investigated the associations of trajectories of cigarette smoking over the high school years with the prior development of childhood sensation seeking and the subsequent use of cigarettes and hookah at age 20/21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 57 publications
1
34
0
2
Order By: Relevance
“…3,8 Our analysis yielded smoking trajectory classes consistent with previous studies using similar methods, supporting the validity of our findings. 18,19,40,41 An important contribution of our study is the attention to nicotine dependence in identifying adolescent smoking trajectories. One study examined how nicotine-dependence symptoms develop among adolescent smokers, concluding that parental smoking increases the risk of early-onset dependence.…”
Section: Discussionmentioning
confidence: 99%
“…3,8 Our analysis yielded smoking trajectory classes consistent with previous studies using similar methods, supporting the validity of our findings. 18,19,40,41 An important contribution of our study is the attention to nicotine dependence in identifying adolescent smoking trajectories. One study examined how nicotine-dependence symptoms develop among adolescent smokers, concluding that parental smoking increases the risk of early-onset dependence.…”
Section: Discussionmentioning
confidence: 99%
“…High initiation levels of TNCPs may be due to demographic (mostly male, low income) and psychosocial (risk taking, high alcohol consumption) risk factors that are prevalent among military personnel. 10,12,13 Additionally, several environmental factors, such as tobacco industry promotional efforts, the availability of low cost tobacco products in military exchanges and commissaries, and the high stress deployment environment, are other likely contributors to these high levels of initiation. 10,14 Although the military represents a specific population of interest, the public health implications of TNCP use in the military is considerable; the US military is the nation's largest employer, employing approximately 1.4 million active duty personnel and over 700 000 civilian personnel.…”
Section: Introductionmentioning
confidence: 99%
“…These models have the ability to differentiate those who abstain from other potential subgroups of substance users. Previous studies of adolescent substance use have identified between two and eight different trajectory classes of alcohol, tobacco, or marijuana use during adolescence (Cheadle & Sittner Hartshorn, 2012;Cheadle & Whitbeck, 2011;Eassey et al, 2015;Hampson et al, 2013;Huang et al, 2013;Juon et al, 2011;Lynne-Landsman et al, 2010Whitesell et al, 2014). Variation in the number of classes identified is the result of differences in model specifications, age ranges evaluated, frequency of assessments, and other sample-specific factors.…”
Section: Trajectories Of Substance Usementioning
confidence: 99%